HUMAN RESOURCE DEVELOPMENT AND EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT AT BINA MANDIRI PRESTASI UNIVERSITY - Tety Octora Paulina Br Sitohang (Jurnal Ilmiah METADATA, 2026)
This study examines the influence of Human Resource Development (HRD) on employee performance, with organizational commitment serving as a mediating variable at Bina Mandiri Prestasi University. The research aims to analyze both the direct effect of HRD on employee performance and the indirect effect through organizational commitment. A quantitative research design was employed using a survey method. Data were collected through structured questionnaires distributed to university employees using a 5-point Likert scale. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the measurement and structural models simultaneously. The findings indicate that Human Resource Development has a significant positive effect on employee performance. Furthermore, HRD significantly influences organizational commitment, which in turn positively affects employee performance. The results confirm that organizational commitment partially mediates the relationship between HRD and employee performance. These findings suggest that effective HRD initiatives not only enhance employee competence but also strengthen emotional attachment and identification with the institution, thereby improving overall performance. This study contributes to strategic human resource management literature in higher education by providing empirical evidence on the mediating role of organizational commitment. The practical implication emphasizes the need for universities to design integrated HRD programs that foster both competence development and organizational commitment to achieve sustainable institutional performance.